Pemasangan Dan Pemeliharaan Jaringan Komputer Pada Sekolah Menengah Kejuruan Parulian 1 Medan - Sony Bahagia Sinaga; Berto Nadeak (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
The development of computer technology is increasing rapidly, this can be seen in the era of the 80s computer networks are still a puzzle that academics want to answer, and in 1988 computer networks began to be used in universities, companies, now entering this millennium era, especially the world wide internet has become the daily reality of millions of people on this earth. In addition, network hardware and software have completely changed, at the beginning of its development almost all networks were built from coaxial cables, now many of them have been built from fiber optics or wireless communication. Computer network technology is already used in various fields including education. Some schools have computers to speed up the work process, and some even use computer network technology to support the learning process. Currently, many schools have computer networks that integrate local networks into intranet and internet networks. Given the need for computer-based education delivery, computer networks in schools are very helpful in the teaching and learning process and make it easier for students and teachers to access information through the internet. In this training, participants will be taught and accompanied to learn to install computer networks. The purpose of this activity is to provide basic computer network training to students, starting from the introduction of computer networks, the practice of making network cables to the configuration of LAN computer networks. The results obtained in general students quickly mastered the material in the installation of computer networks, this is shown by the results of the pre-test. The importance of the results of this service is used to find out how much ability to absorb/capture the material provided by the instructor.